2022
DOI: 10.1002/bit.28131
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Pseudomonas putida for improved utilization of syringyl aromatics

Abstract: Lignin is a largely untapped source for the bioproduction of value-added chemicals.Pseudomonas putida KT2440 has emerged as a strong candidate for bioprocessing of lignin feedstocks due to its resistance to several industrial solvents, broad metabolic capabilities, and genetic amenability. Here we demonstrate the engineering of P. putida for the ability to metabolize syringic acid, one of the major products that comes from the breakdown of the syringyl component of lignin. The rational design was first applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Genome-scale studies are an essential step in developing a host for industrial uses as they enable the identification of genetic factors associated with complex traits for strain optimization. There are a variety of methods that have been employed including adaptive laboratory evolution (Dragosits & Mattanovich, 2013 ; Lim et al., 2021 ; Mueller et al., 2022 ; Wang et al., 2023 ; Zhan et al., 2023 ), transposon-mediated gene disruption (Tn-Seq) (Bleem et al., 2023 ; Borchert et al., 2023 ; Price et al., 2018 ; Shields & Jensen, 2019 ; Wetmore et al., 2015 ), CRISPR-based modifications including interference (CRISPRi), CRISPR activation (CRISPRa), and base editing (Adli, 2018 ; Lee et al., 2019 ; Li et al., 2016 ; Liu et al., 2022 ; Saber Sichani et al., 2023 ; Silvis et al., 2021 ; Volke et al., 2023 ), and random mutagenesis (Freed et al., 2018 ; Riley & Guss, 2021 ). Herein we will focus on CRISPRi, a recently emerged robust functional genomic screening and selection method (Trivedi et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-scale studies are an essential step in developing a host for industrial uses as they enable the identification of genetic factors associated with complex traits for strain optimization. There are a variety of methods that have been employed including adaptive laboratory evolution (Dragosits & Mattanovich, 2013 ; Lim et al., 2021 ; Mueller et al., 2022 ; Wang et al., 2023 ; Zhan et al., 2023 ), transposon-mediated gene disruption (Tn-Seq) (Bleem et al., 2023 ; Borchert et al., 2023 ; Price et al., 2018 ; Shields & Jensen, 2019 ; Wetmore et al., 2015 ), CRISPR-based modifications including interference (CRISPRi), CRISPR activation (CRISPRa), and base editing (Adli, 2018 ; Lee et al., 2019 ; Li et al., 2016 ; Liu et al., 2022 ; Saber Sichani et al., 2023 ; Silvis et al., 2021 ; Volke et al., 2023 ), and random mutagenesis (Freed et al., 2018 ; Riley & Guss, 2021 ). Herein we will focus on CRISPRi, a recently emerged robust functional genomic screening and selection method (Trivedi et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…58,59 The ability of the engineered P. putida KT2440 to utilize syringic acid had been demonstrated through chromosomal overexpression of VanAB and adaptive laboratory evolution. 60,61 Other aromatic derivatives, such as phenol and guaiacol, can enter the central metabolism through the generation of the platform compound catechol. Catechol is assimilated through ortho-cleavage and meta-cleavage pathway to support the cell growth (Fig.…”
Section: Biological Funnel Pathways Of Different Types Of Aromatic Mo...mentioning
confidence: 99%
“…This enzyme comprises a Rieske domain-containing oxygenase subunit encoded by vanA , and a reductase subunit that encompasses FMN, NADPH, and [2Fe-2S] cluster binding domains encoded by vanB , and providing electron equivalents to enable the enzymatic conversion [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. It was shown that the VanOD encoded by vanAB genes from different bacteria were able to catalyze two types of reaction: methoxy group demethylation at the meta position of VA and analogs such as 3-methoxybenzoate (3-MB), veratrate, or syringate, with concomitant release of formaldehyde; or methyl group hydroxylation in m -toluate, 4-hydroxy-3-methylbenzoate, or 4-hydroxy-3,5-dimethylbenzoate; although, with the exception of veratrate and syringate, none of the analogs have been reported to support cell growth employing this enzyme [ 16 , 18 , 19 , 20 , 21 ]. Alternatively, it has been reported that distinct tetrahydrofolate (H 4 folate)-dependent O-demethylases, analogous to aromatic O-demethylases from anaerobic bacteria, are responsible for VA O-demethylation in Sphingobium sp.…”
Section: Introductionmentioning
confidence: 99%